The Influence of Instagram Social Media and User-Generated Content on Purchase Decision Through Brand Trust at Alligator Roastery Medan - Dwi Sakinah; Endang Sulistya Rini; Yeni Absah (Indonesian Journal Publisher, 2026)
Indonesia ranks fourth globally in coffee production, yet faces challenges in domestic market penetration. This study examines how Instagram social media marketing and User-Generated Content (UGC) influence purchase decisions through brand trust at Alligator Roastery Medan, a specialty coffee business experiencing declining customer visits from 680 daily visitors in 2022 to 420 in 2024. Using quantitative methodology with PLS-SEM analysis on 161 respondents selected through purposive sampling, data were collected via structured questionnaires. Results indicate that Instagram positively influences brand trust (β=0.423, p=0.004) and purchase decisions (β=0.298, p=0.005). UGC significantly affects brand trust (β=0.428, p=0.004) but shows no significant direct effect on purchase decisions (β=0.194, p=0.097). Brand trust mediates both relationships significantly and demonstrates the strongest direct effect on purchase decisions (β=0.456, p=0.000), explaining 80.8% of variance in purchase decisions. Findings suggest that digital marketing strategies must prioritize building brand trust through consistent, authentic content and leveraging consumer-generated content to enhance credibility and drive purchase behavior in the specialty coffee market.